2011
DOI: 10.1163/016942410x525713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Weldling Parameters on Weldline Density and Its Relation to Crack Formation in Welded Scots Pine Joints

Abstract: Exterior use of welded wood laminates without further treatment is not recommended. Frictional welded joints have poor resistance to moisture variation, especially to drying. Therefore, application of welded woods is limited to interior use without exposure to highly variable air humidity. Influences of some welding and wood parameters such as welding pressure, welding time and heartwood/sapwood on weldline density of Scots pine (Pinus sylvestris) joints were investigated. Interdependence between density and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Several studies reported the ability of lignocellulose from wood or annual plants to be assembled/ bonded without adhesive by static methods like thermo-compression, possibly assisted by injection of steam [7,8] or by dynamic processes like vibrational welding at low frequency [9][10][11][12][13][14] or ultrasonic compression [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported the ability of lignocellulose from wood or annual plants to be assembled/ bonded without adhesive by static methods like thermo-compression, possibly assisted by injection of steam [7,8] or by dynamic processes like vibrational welding at low frequency [9][10][11][12][13][14] or ultrasonic compression [15].…”
Section: Introductionmentioning
confidence: 99%
“…This is reflected in the WFP, which yielded a higher share as the tensile-shear strength increased. As mentioned by Vaziri et al (2011), examination of the tensile-shear strengths reveal that adhesion in the welded joint is a function of welding time and most probably passes through various characteristic phases. Similar behaviour occurred in the present study, i.e., the strength improved with increased welding time before encountering a drop after a certain point in time (3.5 s).…”
Section: Resultsmentioning
confidence: 88%
“…The thickness of the welded zone also varies as a function of the maximum temperature reached during welding, whilst the maximum temperature reached at the ends of the specimen has been found to be lower than that in the central part of the specimen (Ganne-Chedeville et al 2006). According to Vaziri et al (2011), the degree of densification at the weld line varies from 160 to 190% of the untreated wood density. According to Properzi et al (2005), bond line strength is influenced by the orientation of the wood grain on the two bonding surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of densification of weld lines (weld line density divided by the non-welded wood density) for the heartwood specimens was lower than that for the sapwood samples of Scots pine. Furthermore, the water-resistance of weld lines seemed to be independent of the density of weld lines (Vaziri et al 2011b), which is usually twice the density of the wood pieces welded (Ruponen et al 2015).…”
Section: Effect Of Welding Timementioning
confidence: 99%